Technologies and environmental education: A beneficial relationship - Antonio Hernández Fernández; Claudia De Barros Camargo; Maria Selma Lima Do Nascimento (Research in Social Sciences and Technology, 2019)
Educational technologies have an important role in education today. They represent a relevant resource in the process between theorizing and educational practices, and they are essential in the awareness process for sustainability. Thus, technological education appears as a facilitator in this process, especially with students, parents, and everyone around us, as being supported by tech resources to produce an efficient effect. This study was performed at Escola Municipal de Ensino Fundamental in Alagoinha-Paraíba, Brazil, between January and February, 2019; the research question is: Are teachers using and recognizing technology as a partner in the environmental awareness process? The main objective is to analyze the usage of tech in the process for environmental awareness by teachers. The specific objectives are: to check the usage of technological education in the environmental awareness process, to comprehend the challenges faced by the teachers in the process of technological usage on the scope of environmental education, to identify the activities developed by the teachers involving tech and environmental education, and to perceive the educational practices. A total of 22 teachers responded to the questions. Data collection was made on a Likert scale using the qualitative method and descriptive research. The Likert scale was validated on its construction with analysis factor. Therefore, it was found that the teachers use the tech resources in their classes, through the environmental awareness, besides defending the educational projects and realizing interdisciplinary works about environmental education for environmental conservation.